THE EFFECT OF USING PICTURES ON STUDENTS' ACHIEVEMENT IN ENGLISH LANGUAGE VOCABULARY AT MUHAMMADIYAH UNIVERSITY OF BONE - GUNAWAN GUNAWAN (Universitas Muhammadiyah Makassar, 2022)
English is now a subject studied at primary school until university level. That is because English is essential to students. The main purpose of this study was to determine how pictures affected the students’ ability in English vocabulary. The study's subjects were the English students at Muhammadiyah University of Bone. Only fifteen students were used in the study. The research focused on pre-experimental design. The experiment was conducted to evaluate the effect of the implementation of the picture on vocabulary learning. The researcher used a vocabulary test as the instrument.The outcome demonstrated that utilizing pictures to teach vocabulary can help students' vocabulary. Through the use of pictures, the students mastered vocabulary. The students' vocabulary t-test gives a result of 14,716, which is higher than the t-test value of 2.144. The significant difference in the student's test results between pre- and post-treatment periods (using the image).The analysis of the data revealed that the average score of the post-test (79) was higher than the mean score of the pretest (32).For the level of significance (a) = 0.05 and degree of freedom (df) = 14, then the value of t-table was 14,716, while the t-test value was greater than t-table (14,7162.144). It can be concluded that there was not enough evidence to reject the alternative hypothesis (Ha) in this research. Therefore, the pictures' implied meaning can encourage students to comprehend the text